PENGARUH MODEL LEARNING CYCLE 5E BERBANTUAN MEDIA BENDA KONKRET TERHADAP HASIL BELAJAR IPA PESERTA DIDIK KELAS V - Marisa Ariesta; Ahmad Harjono; Husniati Husniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
This study aims to determine the effect of the 5E learning cycle model assisted by concrete media objects on the learning outcomes of natural science students in class V SDN Gugus IV Praya in the academic year of 2019/2020. This research is quasi-experimental design research with a nonequivalent control group design. The sampling technique used was purposive sampling. The population in this study were students of class V SDN Gugus IV Praya. While the samples in this study were students in class V SDN Gerintuk as an experimental class and SDN 2 Wakul as a control class. The mean value of the experimental class was 74.92 and the control class was 69.66. The learning outcomes data (posttest) were normality tested using the help of SPSS 21.0 for windows program using the Kolmogorov-Smirnov’s one sample formula, then tested for homogeneity using the Levene’s test formula. The test shows that the data is normally distributed and has a homogeneous variant. Furthermore, the data were analyzed using the independent sample t-test formula, the tcount value of 2.335 obtained at a significance level of 5%, the results obtained were ttable of 2.014 so tcount> ttable = 2.335> 2.014 so it can be concluded that Ha was accepted and H0 was rejected. This shows that there is an effect of the 5E learning cycle model assisted by concrete media objects on the learning outcomes of Class V of Science Major students of SDN Gugus IV Praya in the academic year of 2019/2020.